César Dávila Andrade: entre el poeta-sujeto y el sujeto empírico (Legados: Centenario del natalicio de César Dávila Andrade, el Faquir, Cuenca, 1918-Caracas, 1967) - Serrano Sánchez, Raúl Eduardo (2018)
This text examines the irruption in the concert of the avant-garde of Ecuadorian and Latin American poetry of the 1930’s decade of the 20th century by a very young Dávila Andrade, with a poem whose maturity and audacity does not cease to amaze both people and strangers to date; also the impact that his early and lucid poetic exercise produced in the social and cultural environment of his city of origin, Cuenca, as well as his condition as a subject that always knew how to move in what the author of the article, citing Eugenio Montale, defines as between “the poet-subject and the empirical subject”.